"Return of the Ikoi-Koi": Manifestations of Liminality on Nigerian Television - Lyons, Andrew P.; Lyons, Harriet D. (Anthropologica, 2022)
As Victor Turner indicated, liminality and communitas may be present in diverse cultural performances in modern cities. This article examines manifestations of anti-structure in a popular television drama series in Benin City, Nigeria, whose theme has been described as "the class struggle." This drama series is titled "Hotel de Jordan," and lampoons, inter alia, rich men, native doctors, and government officials. The role of liminality in plot, language, and characterization is explored. There is a detailed analysis of an episode which utilizes collective representations concerning ghosts and shades to construct an allegory for the social drama in Nigeria which culminated in a military coup d’etat in December 1983.